Surgical adverse events: a systematic review. - Anderson, O; Davis, R; Hanna, G; Vincent, C (2013)
BACKGROUND: The aim of this systematic review is to quantify potentially preventable patient harm from the frequency, severity, and preventability of the consequences and causes of surgical adverse events to help target patient safety improvement efforts. DATA SOURCES: Two authors independently reviewed articles retrieved from systematic searches of the Cochrane library, MEDLINE, Embase, PsycINFO, and Cumulative Index to Nursing and Allied Health Literature databases for inclusion and exclusion criteria, methodology, and end points. All retrospective record review studies of adverse events were included. The primary end point was the frequency of general surgery adverse events. The secondary end points were the severity and preventability of consequences and causes. CONCLUSIONS: Fourteen record review studies incorporating 16,424 surgical patients were included. Adverse events occurred in 14.4% of patients (interquartile range [IQR], 12.5% to 20.1%), and potentially preventable adverse events occurred in 5.2% (IQR, 4.2% to 7.0%). The consequences of 3.6% of adverse events (IQR, 3.1% to 4.4%) were fatal, those of 10.4% (IQR, 8.5% to 12.3%) were severe, those of 34.2% (IQR, 29.2% to 39.2%) were moderate, and those of 52.5% (IQR, 49.8% to 55.3%) were minor. Errors in nonoperative management caused more frequent adverse events than errors in surgical technique.